The development of metropolises in Germany and France - Christophe Demazière; Patricia Feiertag; Didier Paris; Karsten Zimmermann; Jérôme Dubois (Cities and metropolises in France and Germany, 2022)
The evolution of city regions and metropolises in both countries illustrates the theoretical debates on this particular geographical object. Political legitimacy, significant autonomy and a 'relevant' territorial area should form the basis of these regions. But there is a long way to go from this theoretical vision to practice. In Germany, a slow and contingent bottom-up process can be observed, whereas in France, following a long history of intermunicipality, institutional metropolises are emerging (MAPTAM law of 2014). Metropolregionen and métropoles thus differ. Germany shows incomplete and variable forms of metropolitan organisation, whereas French metropolises are satisfied with simple criteria of competences and resources. However, these 'intermunicipal' métropoles (one exception: Lyon) can also be compared with the large German cities, which are highly individualised political entities, with the city-states (e. g. Hamburg) being the most extreme cases. Two examples, Frankfurt and Lille, illustrate the comparison.
urn:nbn:de:0156-1119047; hdl:10419/266400; https://econpapers.repec.org/RePEc:zbw:arlfob:20
Keywords: 710; Metropolises; governance; local power; Frankfurt; Lille